El divorcio de mutuo disenso disulto por vía administrativa en el registro civil y su congruencia con los principios constitucionales de celeridad, simplificación y economía procesal. - Sandoval Tixelema, Ney Freddy (2012)
The present Investigation has a lot of relevance in the legal field, as regards the termination of the marriage bond in the Civil Registry. It is supported due and motivated with the contribution of several scientific theories of renowned jurists and students of Civil Law. The first chapter, refers to the formulation and delimitation of the problem, is proposed as the main objective to base the divorce trial by mutual consent, according to the constitutional principles in force, determining for the development of this, the general and specific objectives, contains in addition, the hypothesis and its variables that in turn were duly verified during the field investigation. The second chapter refers to the Theoretical Framework that is divided into three sub chapters; The Historical framework, related to the social genesis of marriage through time. The Doctrinal framework refers to the thoughts of several civil law scholars. The Legal Framework is constituted on the basis of Legal grounds, citing in a relevant manner the current Constitution, the Universal Declaration of Human Rights, the Civil Code and other laws that guarantee the rights of individuals; the comparative law of some international legislations is mentioned in this sub chapter, among them that of Mexico, Chile, Portugal, among others. The third chapter refers to the methodology used in the development of legal research, identifying the tools that were essential to gather the information of all the actors and participants in this research process. The fourth chapter presents the proposal developed on the basis of all the legal arguments, in which, firmly convinced of the legal support, I propose "The Project of Amendment to the Law of Civil Registry, Identification and Identification", so that in the cases of Divorce by mutual consent dissolved by administrative means, are in accordance with the constitutional principles of speed, simplification and procedural economy. The fifth chapter refers to the conclusions and recommendations, which were developed with the aim of contributing to the improvement of the system of administering justice, in strict adherence to constitutional principles.